Livros didáticos do PNLD Campo e epistemologias campesinas - Ana Paula da Silva Rodrigues (2019)
The creation of PNLD Campo3 occurs in Brazil as an initiative whose purpose is to contemplate, in textbooks, the specificities of students who study in rural schools. Based on theoretical references on Rural Education (ANTUNES-ROCHA, 2009, ARROYO, 1999 and 2010; CALDART, 2009) on TextBooks (APPLE, 1995 and 2001; BITTENCOURT, 2009; CHOPPIN, 2004; BATISTA & ROJO, 2005 , SOARES, 1996), and also on Critical Interculturality (SANTOS & MENESES, 2010; MAHER, 2007), this research analyzes how the matter of rural specificity is represented in the pedagogical material of PNLD Campo. More specifically, it is sought to describe and analyze the context of emergence and interruption of the PNLD Campo; to verify how or if these books materialize the objectives of the PNLD Campo in its approach to contents and activities; and, finally, to describe and analyze a context of teachers’ response to the approved collections. In order to reach the objectives listed above, a qualitative approach was proposed (BOGDAN & BIKLEN, 1994) and a Case Study (ANDRÉ, 2008) was carried out in a municipality of the Metropolitan Region of Minas Gerais, Brazil. The research collected data in a corpus composed of official documents, collections approved in the two editions of PNLD Campo, application of questionnaires and semi-structured interviews with school teachers from the rural area of the municipality surveyed. For the analysis of the data, we opted for Documentary Analysis (LUDKE and ANDRE, 1986), Content Analysis (BARDIN, 2010), and Discourse Analysis (FAIRCLOUGH, 2012). The results show that, although it has been noticed an effort from the publishers to contemplate the specificities expected for PNLD Campo, the volumes analyzed still lack a greater plurality that would be capable of portraying diversity and interculturality. On the other hand, this is not considered a limitation only of the PNLD Campo, but also of the National Program of Text Books as a whole, which, by universalizing concepts, conceptions, and representations about those subjects and their lifestyles, silence epistemologies that deviate from the euro-urban-centric standard.